Abductor and adductor strength relation to sprint performance in soccer players - Paulina KROLIKOWSKA; Artur GOLAS; Petr STASTNY; Kajub KOKSTEJN; Wojciech GRZYB; Michal KRZYSZTOFIK (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2023)
Introduction: The hip muscle strength plays an important role in sprinting and non-contact injuries, where their role in soccer players needs to be recognized. This study aimed to examine the relationship between the strength of hip abductor (Abd), hip adductor (Add) and linear sprint performance (5 m and 35 m). Sixteen professional soccer players (Second Polish League) participated in the study (age = 24 ± 3.2 years, body mass = 75.3 ± 9.58 kg, height = 179 ± 5.6 cm, soccer training experience = 8 ± 2.9 years). 5 m and 3 m linear sprint performance was described by: peak acceleration, peak velocity (PV), relative peak force (PF), and relative peak power output. Hip Abd and Add strength was tested by maximum isometric tests on both lower limbs. T-tests revealed statistically significant differences between strength of right and left Add and Abd, (p < 0.001, for both). Stepwise regression showed that the model of hip Abd, Add and their ratio predict the PV (R2 = 37%) and PP (R2 = 36%) in 35 m sprint, and hip Abd with Abd/Add ratio can predict PF (R2 = 16%) and acceleration (R2 = 14%) in 5 m sprint. Results of the present study indicate that Abd-Add maximum isometric strength and 5 m, as well as 35 m sprint running, are related athletic performance qualities. Moreover, hip Abd and Add are typical for strength bilateral strength imbalances. Therefore, the evaluation and development of these qualities are essential for coaches to monitor and prescribe adequate training regimens.